PECULIARITIES OF WEB APPLICATIONS DEVELOPING FOR THE DISTANCE LEARNING SYSTEM USING THE REACT LIBRARY - Koshova, O. P.; Chernenko, O. O.; ChilikinaТ. V.; Komar, I. I. (Systems and Technologies, 2023)
The paper considers the features of the development of a distance learning system for students of higher education establishment using the TypeScript programming language and the React library. It has been proved that the remote form of education best corresponds to the peculiarities of the training of students majoring in “Computer Science”. The most famous existing distance learning systems were analyzed, namely: Moodle Blackboard Google Classroom Canvas. Their functionality and opportunities for the work of teachers and students are highlighted. Disadvantages and advantages of each system are considered. In order for students of the “Computer Science” specialty to acquire the necessary skills and competences for future professional activities, the pedagogical conditions for their training using the distance learning system are singled out, namely: the need to combine the traditional style of teaching disciplines with information and innovative learning technologies, which will ensure systematicity and functionality acquired knowledge, skills and abilities; introduction of laboratory forms of practical classes and information technologies based on applied programs. It is shown that the development of a distance learning system is one of the practice-oriented tasks. According to the results of the analysis of systems of a similar purpose, carried out in our research, we chose for the development of elements of the distance learning system: service for the development of interfaces and prototyping Figma; TypeScript programming language; CSS preprocessor Sass; libraries: React, Redux, Redux-Saga, Zod; Git version control system. The project is implemented in the TypeScript programming language using the React library. A UML diagram of precedents of the developed distance learning system was built, containing precedents for actors: authorized user, unauthorized user, user, teacher and administrator. Precedents are as follows: login, view own courses, view gradebook, view own files, view profile settings, view list of courses taught, view course, view topics, view materials, view course settings, view users. The advantages and features of using the React library to create a distance learning system are analyzed. Using the React library, a distance learning system was developed, according to the precedent diagram, namely: Teacher Pages and Student Pages with corresponding functions and capabilities.